EFFECT OF PLANTING RATE AND HARVESTING DATES ON GREEN MASS YIELD OF PERENNIAL AND MULTI-CROP GRASS SORGHUM - Yuldasheva Zulfia Kamalovna; Mirzaev Pardaboy Odiljon ugli (Western European Studies, 2023)
In the article, the effect of sowing rate and harvesting period on the green mass yield of perennial and multi-fertile grassy sorghum (Kolusb grass) variety "Azamat" is studied. In the variant with 4.0 kg of seed per hectare, the yield of 182.1 tons of green mass was obtained compared to the experimentally low and increased sowing rate at the end of the flowering phase.
Keywords: Grassy sorghum; multi-harvest; green mass; first harvest; second harvest; yield